A Day in the Life: Personas of Professional Communicators at Work. (July 2020) - Brumberger, Eva; Lauer, Claire
This article uses personas to illustrate the range of technical communication knowledge work developed through its practitioners—to articulate the functions, characteristics, traits, skills, and workplace styles of positions someone in the field might pursue. Recent research has provided valuable data about the expanding and evolving skill sets of the technical/professional communicator. We build on that by triangulating the data from an analysis of job postings, a survey of technical communicators, and interviews and embedded observations of practitioners to develop personas of technical/professional communicators on the job. The personas can help students, programs, and practitioners understand and navigate the many types of roles that are available in the field.